1997
DOI: 10.1006/jabr.1996.6818
|View full text |Cite
|
Sign up to set email alerts
|

Asymptotic Results for Primitive Permutation Groups

Abstract: We prove that the number of conjugacy classes of primitive permutation groups cŽ n.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 36 publications
0
19
0
Order By: Relevance
“…It can be shown that this number is bounded above by n c log n for all n, and bounded below by n c$ log nÂlog log n for infinitely many values of n [PSh2]. See also [P], [PSh1] for related results, and for applications of estimates of this type to subgroup growth of infinite groups.…”
Section: Introductionmentioning
confidence: 96%
“…It can be shown that this number is bounded above by n c log n for all n, and bounded below by n c$ log nÂlog log n for infinitely many values of n [PSh2]. See also [P], [PSh1] for related results, and for applications of estimates of this type to subgroup growth of infinite groups.…”
Section: Introductionmentioning
confidence: 96%
“…By [34], if G is a primitive permutation group of degree n > 2, then there is a constant a such that d(G) ≤ a log n/ √ log log n. Now, applying Theorem 8.1, we obtain the desired result. Corollary 8.2 improves an n c log n bound which is the main result of [49]. Note that for infinitely many positive integers n even, the number of isomorphism types of primitive soluble groups is at least n log n log log n [49].…”
Section: Corollary 82mentioning
confidence: 71%
“…Corollary 8.2 improves an n c log n bound which is the main result of [49]. Note that for infinitely many positive integers n even, the number of isomorphism types of primitive soluble groups is at least n log n log log n [49].…”
Section: Corollary 82mentioning
confidence: 71%
See 1 more Smart Citation
“…We refer to the surveys of Cameron [4] and Pyber [17,18] and the recent paper by Pyber and Shalev [19] for a detailed exposition of this subject. In this paper we concentrate our attention on the number of generators.…”
mentioning
confidence: 99%